Criminal evidence - Roberts, Paul (Oxford university press, 2004)
This work offers a critical commentary on the main rules and principles regulating the admission of evidence in English criminal proceedings. Existing legal rules are placed in their theoretical, institutional, procedural, and broader criminal justice context, and reform options are systematically canvassed and examined